Listening and the ambiguities of voice in South African journalism. Issue 1 (2nd January 2017) - Garman, Anthea; Malila, Vanessa
ABSTRACT: Political theorists like Bickford (1996) and media theorists like Couldry (2006) have introduced the concept of listening as a complement to long-standing discussions about voice in democracies and in the media which serve the democratic project. This enhanced understanding of voice goes beyond just hearing into giving serious attention to, in particular, marginalised voices. This article reports on an investigation into the ways in which mainstream and community media in the Eastern Cape, South Africa, understand listening as an important part of their role as journalists. Interviews probed the attitudes of journalists and editors towards listening, and also interrogated their own understandings of their role in South Africa, particularly in relation to young people who are finding their political "voice". The research showed that "listening" as a journalistic practice is seldom understood in anything more than common sense ways and is certainly not an organising principle of reporting and disseminating news. This results in journalism that is events focused, often sensationalist and whose agenda is set powerfully by political actions and actors in the environment. The power of being heard is almost solely in the hands of the journalists, who regard themselves as "the voice of the people", without actively providing a space for listening to the voices of community members. But, within this generalised environment, there are two very interesting projects in which journalists and editors are actively listening to the issues and stories of citizens and letting them set agendas.